Basalt fiber modified cement-based capillary crystalline waterproof coating storage tank and method

By using basalt fiber modified cement-based permeable crystalline waterproof coating in cement-based storage tanks, the problems of poor crack resistance, low toughness and insufficient durability of cement-based storage tanks are solved, and efficient waterproofing performance and long-term stability are achieved. Use effect.

CN119432135APending Publication Date: 2025-02-14YUNNAN XINCHENG WATERPROOF TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411584582.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing cement-based storage tanks are prone to cracks under temperature changes and external stress, resulting in a decrease in sealing properties and increasing the risk of leakage. At the same time, their crack resistance is poor, low toughness and insufficient durability.

Method used

Use basalt fiber to modify cement-based permeable crystalline waterproof coatings, and add basalt fibers, permeable crystalline additives, polymer emulsions and anti-ultraviolet agents to the cement-based materials to form a coating with high tensile strength and toughness. And crystals are formed by permeating crystalline additives to enhance waterproofing properties.

Benefits of technology

It significantly improves the crack resistance and toughness of the coating, extends the service life of the storage tank, improves the waterproofing effect, reduces the risk of water damage, and maintains long-term and stable performance in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432135A_ABST
    Figure CN119432135A_ABST
Patent Text Reader

Abstract

The invention relates to the field of waterproof coating storage tanks, and discloses a basalt fiber modified cement-based permeable crystallization type waterproof coating storage tank and a method, the basalt fiber modified cement-based permeable crystallization type waterproof coating storage tank comprises the following raw materials by mass: 40-50 parts of cement, 5-10 parts of basalt fiber, 30-40 parts of sand, 20-25 parts of water, 5-10 parts of a permeable crystallization type additive, 10-15 parts of a polymer emulsion, 1-2 parts of a mildew inhibitor, 1-3 parts of a thickener, 1-3 parts of a rheology modifier, and 5-10 parts of a filler, the length of the basalt fiber is 6 to 12mm, and the diameter of the basalt fiber is 9 to 13 microns. The cement-based material is modified by using the basalt fiber, and the basalt fiber has the characteristics of excellent mechanical property and high temperature resistance, so that the crack resistance of the coating can be effectively enhanced, cracks caused by temperature change and external stress are reduced, the service life of the storage tank is prolonged, and the tensile strength and toughness of the coating are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of waterproof coating storage tanks, in particular to a basalt fiber modified cement-based permeable crystallization waterproof coating storage tank and a method. Background Art

[0002] Cement-based storage tanks are widely used in industrial and civil fields, mainly for storing liquids and solid materials. These tanks are usually used to store water, chemicals, petroleum products, food and beverages, etc., and are favored for their good structural strength and durability. Cement-based storage tanks can withstand environmental changes, withstand internal pressure, and prevent liquid leakage to a certain extent, ensuring the safety and stability of stored materials.

[0003] However, as time goes by and the temperature changes, there are some obvious deficiencies, which are mainly reflected in the following aspects:

[0004] Poor crack resistance: Cement-based materials are prone to cracks due to temperature changes, external stress and aging, which leads to reduced sealing of the tank and increased risk of leakage. Low toughness: The brittleness of traditional cement-based materials makes them easy to crack when subjected to impact or deformation, and cannot effectively protect the internal storage medium. Insufficient durability: During long-term use, the performance of cement-based storage tanks will degrade due to factors such as water penetration and chemical corrosion, affecting the service life of the tank. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a basalt fiber modified cement-based permeable crystallization waterproof coating storage tank and method, which solves the problems in the prior art that cement-based storage tanks have poor crack resistance, low toughness and insufficient durability as time goes by and the temperature changes.

[0006] To achieve the above purpose, the present invention is implemented by the following technical scheme: basalt fiber modified cement-based penetrating crystalline waterproof coating, the coating is used to coat the storage tank, including the following raw materials, calculated by mass:

[0007] 40-50 parts of cement

[0008] Basalt fiber 5-10 parts

[0009] 30-40 parts of sand

[0010] 20-25 parts water

[0011] 5-10 parts of penetrating crystallization additive

[0012] 10-15 parts polymer emulsion

[0013] 1-2 parts of antifungal agent

[0014] Thickener 1-3 parts

[0015] Rheology modifier 1-3 parts

[0016] Filler 5-10 parts

[0017] 1 to 2 parts of anti-ultraviolet agent.

[0018] Preferably, the cement is silicate cement, and the basalt fiber has a length of 6 to 12 mm and a diameter of 9 to 13 μm.

[0019] Preferably, the sand used is medium-coarse sand with a particle size of 0.5 to 1.0 mm, and the water is clean drinking water with no impurities and a pH value of 6 to 8.

[0020] Preferably, the penetrating crystallization additive uses a cement-based crystalline waterproofing agent, the polymer emulsion uses an acrylic emulsion, and the mildew preventer uses chlorobenzene glycol.

[0021] Preferably, the thickener is sodium carboxymethyl cellulose thickener, and the rheology modifier is a polyurethane modifier.

[0022] Preferably, the filler is talcum powder, and the anti-ultraviolet agent is titanium dioxide.

[0023] The method for manufacturing a basalt fiber modified cement-based permeable crystallization waterproof coating storage tank comprises the following steps:

[0024] S1. Prepare raw materials, including cement, basalt fiber, sand, water, osmotic crystallization additive, polymer emulsion, mildew inhibitor, thickener, rheology modifier, filler and UV inhibitor;

[0025] S2, mixing cement, sand, basalt fiber and filler in a mixer;

[0026] S3, adding thickener, rheology modifier, mildew inhibitor and anti-ultraviolet agent into a mixer and mixing evenly;

[0027] S4, gradually add water and polymer emulsion, and continue stirring until a uniform coating is formed;

[0028] S5. Apply the prepared coating to the inner wall of the storage tank to ensure uniform coating;

[0029] S6. Carry out curing and maintenance, and maintain temperature and humidity conditions.

[0030] Preferably, in S2, the stirrer speed is 150-200RPM, and the stirring time is 3-5min to ensure uniform mixing. In S3, the stirrer speed is 150-200RPM, and the stirring time is 2-3min.

[0031] Preferably, in S4, the speed of the stirrer is 100 to 150 RPM, and the stirring time is 5 to 7 minutes, until the coating reaches a uniform and particle-free state.

[0032] Preferably, in S5, the coating thickness is 1 to 2 mm, in S6, the curing time is 7 to 8 days, the curing temperature is 20 to 30° C., and the relative humidity is maintained at 60 to 80%.

[0033] The invention provides a basalt fiber modified cement-based permeable crystallization waterproof coating storage tank and method.

[0034] It has the following beneficial effects:

[0035] 1. The present invention uses basalt fiber to modify cement-based materials. By utilizing the excellent mechanical properties and high temperature resistance of basalt fiber, the crack resistance of the coating can be effectively enhanced, cracks caused by temperature changes and external stress can be reduced, the service life of the storage tank can be extended, and the tensile strength and toughness of the coating can be significantly improved.

[0036] 2. The present invention utilizes a penetrating crystallization additive to enable the coating to form crystals during the hardening process and fill tiny pores, thereby greatly improving the waterproof effect, enabling the storage tank to effectively resist water penetration, protecting the internal medium, and reducing the risk of water damage.

[0037] 3. By adding polymer emulsion and UV inhibitor to the coating, the present invention can make the modified coating show excellent durability under harsh environmental conditions, so that the coating can effectively resist ultraviolet rays, moisture and temperature changes, thereby maintaining long-term stable performance and being suitable for a variety of industrial environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 It is a flow chart of the manufacturing steps of the present invention; DETAILED DESCRIPTION

[0039] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] Please refer to the attached Figure 1The embodiment of the present invention provides a basalt fiber modified cement-based penetrating crystallization waterproof coating, which is used for coating storage tanks and includes the following raw materials, calculated by weight: 40-50 parts of cement, 5-10 parts of basalt fiber, 30-40 parts of sand, 20-25 parts of water, 5-10 parts of penetrating crystallization additive, 10-15 parts of polymer emulsion, 1-2 parts of mildewproof agent, 1-3 parts of thickener, 1-3 parts of rheology modifier, 5-10 parts of filler, and 1-2 parts of UV inhibitor.

[0041] Portland cement is used as cement, and the length of basalt fiber is 6 to 12 mm and the diameter is 9 to 13 μm.

[0042] The sand used is medium-coarse sand with a particle size of 0.5 to 1.0 mm. The water used is clean drinking water with no impurities and a pH value of 6 to 8.

[0043] The penetrating crystallization additive uses a cement-based crystalline waterproofing agent, the polymer emulsion uses an acrylic ester emulsion, and the mildew preventer uses chlorobenzene glycol.

[0044] The thickener is sodium carboxymethyl cellulose, and the rheology modifier is polyurethane.

[0045] The filler is set to talc and the UV inhibitor is titanium dioxide.

[0046] The method for manufacturing the above storage tank comprises the following steps:

[0047] S1. Prepare raw materials, including cement, basalt fiber, sand, water, osmotic crystallization additive, polymer emulsion, mildew inhibitor, thickener, rheology modifier, filler and UV inhibitor;

[0048] S2, mixing cement, sand, basalt fiber and filler in a mixer;

[0049] S3, adding thickener, rheology modifier, mildew inhibitor and UV inhibitor into a mixer and mixing evenly;

[0050] S4, gradually add water and polymer emulsion, and continue stirring until a uniform coating is formed;

[0051] S5. Apply the prepared coating to the inner wall of the storage tank to ensure uniform coating;

[0052] S6. Carry out curing and maintenance, and maintain temperature and humidity conditions.

[0053] In S2, the mixer speed is 150-200 RPM and the stirring time is 3-5 min to ensure uniform mixing. In S3, the mixer speed is 150-200 RPM and the stirring time is 2-3 min.

[0054] In S4, the mixer speed is 100-150 RPM and the stirring time is 5-7 minutes, until the coating reaches a uniform and particle-free state.

[0055] In S5, the coating thickness is 1 to 2 mm, in S6, the curing time is 7 to 8 days, the curing temperature is 20 to 30° C., and the relative humidity is maintained at 60 to 80%.

[0056] Embodiment 1:

[0057] step:

[0058] Prepare the raw materials: cement (45 parts), basalt fiber (10 parts), sand (30 parts), water (22 parts), penetrating crystallization additive (8 parts), polymer emulsion (12 parts), mildew inhibitor (1.5 parts), thickener (2 parts), rheology modifier (2 parts), filler (6 parts), and UV inhibitor (1.5 parts).

[0059] Cement, sand, basalt fiber and filler were mixed in a mixer at 150 RPM for 4 minutes.

[0060] Add thickener, rheology modifier, mildew inhibitor and UV inhibitor at 150 RPM for 3 minutes.

[0061] Water and polymer emulsion were gradually added at 100 RPM for 6 minutes.

[0062] Apply the coating to the inner wall of the tank with a thickness of 2 mm and cure for 7 days.

[0063] Summary: By increasing the proportion of basalt fiber, the tensile strength and toughness of the coating are significantly improved, and cracks caused by external stress are reduced. It is suitable for storage tanks that require high crack resistance.

[0064] Embodiment 2:

[0065] step:

[0066] Prepare the raw materials: cement (45 parts), basalt fiber (7 parts), sand (35 parts), water (22 parts), penetrating crystallization additive (10 parts), polymer emulsion (12 parts), mildew inhibitor (1.5 parts), thickener (2 parts), rheology modifier (2 parts), filler (6 parts), and UV inhibitor (1.5 parts).

[0067] Cement, sand, basalt fiber and filler were mixed in a mixer at 150 RPM for 4 minutes.

[0068] Add thickener, rheology modifier, mildew inhibitor and UV inhibitor at 150 RPM for 3 minutes.

[0069] Water and polymer emulsion were gradually added at 100 RPM for 6 minutes.

[0070] Apply the coating to the inner wall of the tank with a thickness of 2 mm and cure for 7 days.

[0071] Summary: Increasing the proportion of penetrating crystalline additives significantly improves the waterproof performance of the coating. The coating can effectively close the pores, improve impermeability, and is suitable for use in humid environments.

[0072] Embodiment three:

[0073] step:

[0074] Prepare the raw materials: cement (45 parts), basalt fiber (7 parts), sand (35 parts), water (20 parts), penetrating crystallization additive (8 parts), polymer emulsion (15 parts), mildew inhibitor (1.5 parts), thickener (2 parts), rheology modifier (2 parts), filler (6 parts), and UV inhibitor (1.5 parts).

[0075] Cement, sand, basalt fiber and filler were mixed in a mixer at 150 RPM for 4 minutes.

[0076] Add thickener, rheology modifier, mildew inhibitor and UV inhibitor at 150 RPM for 3 minutes.

[0077] Water and polymer emulsion were gradually added at 100 RPM for 6 minutes.

[0078] Apply the coating to the inner wall of the tank with a thickness of 2 mm and cure for 7 days.

[0079] Summary: The addition of polymer emulsion improves the flexibility and adhesion of the coating, can effectively resist the stress caused by temperature changes, and is suitable for environments with large temperature differences.

[0080] Embodiment 4:

[0081] step:

[0082] Prepare the raw materials: cement (45 parts), basalt fiber (7 parts), sand (35 parts), water (22 parts), penetrating crystallization additive (8 parts), polymer emulsion (12 parts), mildew inhibitor (1.5 parts), thickener (2 parts), rheology modifier (2 parts), filler (6 parts), and UV inhibitor (2 parts).

[0083] Cement, sand, basalt fiber and filler were mixed in a mixer at 150 RPM for 4 minutes.

[0084] Add thickener, rheology modifier, mildew inhibitor and UV inhibitor at 150 RPM for 3 minutes.

[0085] Water and polymer emulsion were gradually added at 100 RPM for 6 minutes.

[0086] Apply the coating to the inner wall of the tank with a thickness of 2 mm and cure for 7 days.

[0087] Summary: Increasing the proportion of UV inhibitors significantly enhances the weather resistance of the coating, preventing the coating from degrading due to UV rays, and is suitable for storage tanks outdoors or exposed to direct sunlight.

[0088] Embodiment five:

[0089] step:

[0090] Prepare the raw materials: cement (45 parts), basalt fiber (8 parts), sand (35 parts), water (22 parts), penetrating crystallization additive (9 parts), polymer emulsion (14 parts), mildew inhibitor (1.5 parts), thickener (2 parts), rheology modifier (2 parts), filler (6 parts), and UV inhibitor (1.5 parts).

[0091] Cement, sand, basalt fiber and filler were mixed in a mixer at 150 RPM for 4 minutes.

[0092] Add thickener, rheology modifier, mildew inhibitor and UV inhibitor at 150 RPM for 3 minutes.

[0093] Water and polymer emulsion were gradually added at 100 RPM for 6 minutes.

[0094] Apply the coating to the inner wall of the tank with a thickness of 2 mm and cure for 7 days.

[0095] Summary: In the comprehensive and optimized formula, the proportions of each ingredient have been balanced and adjusted to improve the overall performance of the coating, making it suitable for tank waterproofing needs in a variety of complex environments.

[0096] Summary

[0097] By comparing five different embodiments, it can be concluded that:

[0098] The addition of basalt fiber significantly improves the crack resistance of the coating;

[0099] The increased proportion of penetrating crystalline additives enhances the waterproofing effect;

[0100] The enhancement of polymer emulsion improves the flexibility and adhesion of the coating;

[0101] The addition of UV inhibitors effectively prevents degradation caused by UV rays.

[0102] By optimizing the ratio of each component, the final embodiment shows good comprehensive performance and adapts to different application requirements.

[0103] Test experiments and specific data

[0104] Test parameters: tensile strength, compressive strength, impermeability, crack resistance, abrasion resistance, flexibility and weather resistance.

[0105] Experimental data table:

[0106]

[0107] Specific parameter comparison summary:

[0108] The tensile and compressive strengths of Example 5 are the highest, showing that comprehensive optimization significantly improves performance.

[0109] The anti-seepage performance is the best in Example 2, indicating that the effect of the penetrating crystalline additive is obvious.

[0110] The improvement of the polymer emulsion makes Example 3 outstanding in flexibility and suitable for environments with large temperature differences.

[0111] In terms of weather resistance, Examples 4 and 5 performed well and were suitable for outdoor applications.

[0112] Comparative Experimental Design

[0113] Experimental and control group settings

[0114] Experimental Group 1: Exploring the Effect of Basalt Fiber

[0115] Experimental group: cement (45 parts), basalt fiber (10 parts), sand (30 parts), water (22 parts), penetrating crystallization additive (8 parts), polymer emulsion (12 parts), mildew inhibitor (1.5 parts), thickener (2 parts), rheology modifier (2 parts), filler (6 parts), and UV inhibitor (1.5 parts).

[0116] Control group: cement (45 parts), polypropylene fiber (10 parts), sand (30 parts), water (22 parts), penetrating crystallization additive (8 parts), polymer emulsion (12 parts), mildew inhibitor (1.5 parts), thickener (2 parts), rheology modifier (2 parts), filler (6 parts), and UV inhibitor (1.5 parts).

[0117] Experimental Group 2: Exploring the Effect of Penetrating Crystallization Additives

[0118] Experimental group: cement (45 parts), basalt fiber (7 parts), sand (35 parts), water (22 parts), penetrating crystallization additive (10 parts), polymer emulsion (12 parts), mildew inhibitor (1.5 parts), thickener (2 parts), rheology modifier (2 parts), filler (6 parts), and UV inhibitor (1.5 parts).

[0119] Control group: cement (45 parts), basalt fiber (7 parts), sand (35 parts), water (22 parts), non-crystalline waterproof additive (10 parts), polymer emulsion (12 parts), mildew inhibitor (1.5 parts), thickener (2 parts), rheology modifier (2 parts), filler (6 parts), and UV inhibitor (1.5 parts).

[0120] Experimental Group 3: Exploring the Effect of Polymer Emulsion

[0121] Experimental group: cement (45 parts), basalt fiber (7 parts), sand (35 parts), water (20 parts), penetrating crystallization additive (8 parts), polymer emulsion (15 parts), mildew inhibitor (1.5 parts), thickener (2 parts), rheology modifier (2 parts), filler (6 parts), and UV inhibitor (1.5 parts).

[0122] Control group: cement (45 parts), basalt fiber (7 parts), sand (35 parts), water (20 parts), penetrating crystallization additive (8 parts), ordinary cement-based emulsion (15 parts), mildew inhibitor (1.5 parts), thickener (2 parts), rheology modifier (2 parts), filler (6 parts), and UV inhibitor (1.5 parts).

[0123] Experimental Group 4: Exploring the Effect of Anti-UV Agents

[0124] Experimental group: cement (45 parts), basalt fiber (7 parts), sand (35 parts), water (22 parts), penetrating crystallization additive (8 parts), polymer emulsion (12 parts), mildew inhibitor (1.5 parts), thickener (2 parts), rheology modifier (2 parts), filler (6 parts), and UV inhibitor (2 parts).

[0125] Control group: cement (45 parts), basalt fiber (7 parts), sand (35 parts), water (22 parts), penetrating crystallization additive (8 parts), polymer emulsion (12 parts), mildew inhibitor (1.5 parts), thickener (2 parts), rheology modifier (2 parts), filler (6 parts), and ordinary filler (1.5 parts).

[0126] Test Parameters

[0127] For each set of experiments and controls, the following test parameters will be used: tensile strength, compressive strength, penetration resistance, crack resistance, abrasion resistance, flexibility, and weathering resistance.

[0128] Experimental data table:

[0129]

[0130] Detailed performance analysis

[0131] The following is a detailed analysis of the performance data in the experimental group and the control group:

[0132] 1. Tensile strength (MPa)

[0133] Experimental group 1: 3.5

[0134] Control group 1:3.0

[0135] Analysis: The basalt fibers in Experimental Group 1 significantly improved the tensile strength, indicating that they exhibited better toughness and ductility when subjected to tensile stress. This enhancement effect is mainly attributed to the high strength characteristics of basalt fibers.

[0136] 2. Compressive strength (MPa)

[0137] Experimental group 2: 3.6

[0138] Control group 2: 3.2

[0139] Analysis: The compressive strength of experimental group 2 is higher than that of the control group, indicating that the penetrating crystalline additive enhances the density of the coating, making it more stable when under pressure. This is critical to the structural integrity of the tank.

[0140] 3. Anti-seepage performance (L / m 2 h)

[0141] Experimental group 3: 0.04

[0142] Control group 3: 0.05

[0143] Analysis: The anti-seepage performance of experimental group 3 is better than that of the control group. The reduced water permeability shows that the polymer emulsion improves the density and waterproof effect of the coating, and is suitable for applications requiring higher waterproof performance.

[0144] 4. Crack resistance

[0145] Experimental group 4: no cracks

[0146] Control group 4: with cracks

[0147] Analysis: There were no cracks in experimental group 4, indicating that the use of UV stabilizers effectively prevented material degradation caused by UV rays and maintained the structural integrity of the coating. This result emphasizes the importance of UV stabilizers in outdoor applications.

[0148] 5. Wear resistance (g)

[0149] Experimental group 1:4

[0150] Control group 1:5

[0151] Analysis: Although the wear resistance of experimental group 1 is slightly lower than that of the control group, considering its advantages in tensile and compressive properties, it means that although basalt fiber increases strength, it may compromise wear resistance. This needs to be balanced in practical applications.

[0152] 6. Flexibility (mm)

[0153] Experimental group 3: 2.5

[0154] Control group 3:2.0

[0155] Analysis: The addition of polymer emulsion in experimental group 3 makes the coating more flexible, able to adapt to stress changes caused by temperature changes, and reduce the risk of cracks.

[0156] 7. Weather resistance (hours)

[0157] Experimental group 4:320

[0158] Control group 4:290

[0159] Analysis: The improved weather resistance of experimental group 4 indicates that the addition of UV inhibitors can effectively extend the durability of the coating under UV radiation, thereby reducing material aging caused by UV rays.

[0160] Summarize

[0161] The performance comparison between the experimental group and the control group showed that specific ingredients (such as basalt fibers, penetrating crystallization additives, polymer emulsions and UV stabilizers) contributed significantly to the overall performance improvement of the coating.

[0162] Basalt fiber improves tensile strength and toughness, but is slightly inferior in wear resistance, showing the importance of balancing material properties.

[0163] The penetrating crystalline additive significantly improves the anti-seepage performance and is suitable for waterproof coatings.

[0164] The addition of polymer emulsion improves the flexibility of the coating and ensures stability in extreme climates.

[0165] Anti-UV agents effectively improve weather resistance and extend the service life of the coating.

[0166] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. Basalt fiber modified cement-based penetrating crystalline waterproof coating, characterized in that: The coating is used for coating storage tanks and comprises the following raw materials, calculated by weight: 40-50 parts of cement Basalt fiber 5-10 parts 30-40 parts of sand 20-25 parts water 5-10 parts of penetrating crystallization additive 10-15 parts polymer emulsion 1-2 parts of antifungal agent Thickener 1-3 parts Rheology modifier 1-3 parts Filler 5-10 parts 1 to 2 parts of anti-ultraviolet agent.

2. The basalt fiber modified cement-based penetrating crystallization waterproof coating according to claim 1, characterized in that: The cement is silicate cement, and the basalt fiber has a length of 6 to 12 mm and a diameter of 9 to 13 μm.

3. The basalt fiber modified cement-based penetrating crystallization waterproof coating according to claim 1, characterized in that: The sand used is medium-coarse sand with a particle size of 0.5-1.0 mm, and the water is clean drinking water with no impurities and a pH value of 6-8.

4. The basalt fiber modified cement-based penetrating crystallization waterproof coating according to claim 1, characterized in that: The penetrating crystallization additive uses a cement-based crystallization waterproofing agent, the polymer emulsion uses an acrylic ester emulsion, and the mildew preventer uses chlorobenzene glycol.

5. The basalt fiber modified cement-based penetrating crystallization waterproof coating according to claim 1, characterized in that: The thickener is sodium carboxymethyl cellulose, and the rheology modifier is polyurethane.

6. The basalt fiber modified cement-based penetrating crystallization waterproof coating according to claim 1, characterized in that: The filler is talc powder, and the anti-ultraviolet agent is titanium dioxide.

7. A method for manufacturing a basalt fiber modified cement-based penetrating crystalline waterproof coating storage tank, using the basalt fiber modified cement-based penetrating crystalline waterproof coating according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Prepare raw materials, including cement, basalt fiber, sand, water, osmotic crystallization additive, polymer emulsion, mildew inhibitor, thickener, rheology modifier, filler and UV inhibitor; S2, mixing cement, sand, basalt fiber and filler in a mixer; S3, adding thickener, rheology modifier, mildew inhibitor and anti-ultraviolet agent into a mixer and mixing evenly; S4, gradually add water and polymer emulsion, and continue stirring until a uniform coating is formed; S5. Apply the prepared coating to the inner wall of the storage tank to ensure uniform coating; S6. Carry out curing and maintenance, and maintain temperature and humidity conditions.

8. The method for manufacturing a basalt fiber modified cement-based permeable crystallization waterproof coating storage tank according to claim 7, characterized in that: In the S2, the mixer speed is 150-200RPM, and the stirring time is 3-5min to ensure uniform mixing. In the S3, the mixer speed is 150-200RPM, and the stirring time is 2-3min.

9. The method for manufacturing a basalt fiber modified cement-based permeable crystallization waterproof coating storage tank according to claim 7, characterized in that: In S4, the speed of the mixer is 100-150 RPM, and the stirring time is 5-7 minutes, until the coating reaches a uniform state without particles.

10. The method for manufacturing a basalt fiber modified cement-based permeable crystallization waterproof coating storage tank according to claim 7, characterized in that: In the S5, the coating thickness is 1 to 2 mm, and in the S6, the curing time is 7 to 8 days, the curing temperature is 20 to 30° C., and the relative humidity is maintained at 60 to 80%.

Citation Information

Patent Citations

  • Basalt fiber modified polymer cement waterproof coating

    CN114085585A

  • Capillary crystalline repair mortar suitable for humid environment and preparation method thereof

    CN118619624A